Pengaruh Komposisi Kompos Limbah Jerami Padi dengan Tanah Terhadap Pertumbuhan Tomat Cherry (Solanum lycopersicum var. cerasiforme) di Persemaian - Abdullah, Abdullah; Heiriyani, Tuti; Gazali, Akhmad (Agroekotek View, 2024)
Each planting season, rice straw produced in rice cultivation is also abundant, around 7-10 tons/ha if the rice straw is not managed properly it will cause problems for the surrounding environment. One of the efforts to maximize rice straw management is by composting it. In addition to adding nutrients, compost fertilizer can also improve soil properties that support plant growth. Cherry tomato is a plant that will grow well on sandy loam type soil, fertile, loose, has a high organic matter content, and easily attracts water (porous). This study aims to analyze the effect of rice straw compost with soil as a planting medium on the growth of cherry tomatoes (Solanum lycopersicum var. cerasiforme) in nurseries. This research was conducted from March to April 2020 at the Tanah Laut Dormitory, Banjarbaru, South Kalimantan. Using a single factor completely randomized design (CRD) method with 4 treatments and each treatment was repeated 5 times until 20 experimental units were obtained. The results showed that the composition of the planting medium was 75% soil: 25% compost of rice straw waste showed the best effect on each observation.